A comparative study of identical VMAT plans with and without jaw tracking technique. (8th September 2016) - Wu, Hao; Jiang, Fan; Yue, Haizhen; Hu, Qiaoqiao; Zhang, Jian; Liu, Zhuolun; Gong, Jian; Li, Sha; Geng, Jianhao; Zhang, Yibao
Abstract : The unwanted radiation transmission through the multileaf collimators could be reduced by the jaw tracking technique which is commercially available on Varian TrueBeam accelerators. On the basis of identical plans, this study aims to investigate the dosimetric impact of jaw tracking on the volumetric‐modulated arc therapy (VMAT) plans. Using Eclipse treatment planning system (TPS), 40 jaw‐tracking VMAT plans with various tumor volumes and shapes were optimized. Fixed jaw plans were created by editing the jaw coordinates of the jaw‐tracking plans while other parameters were identical. The deliverability of this artificial modification was verified using COMPASS system via three‐dimentional gamma analysis between the measurement‐based reconstruction and the TPS‐calculated dose distribution. Dosimetric parameters of dose‐volume histogram (DVH) were compared to assess the improvement of dose sparing for organs at risk (OARs) in jaw‐tracking plans. COMPASS measurements demonstrated that over 96.9% of structure volumes achieved gamma values less than 1.00 at criteria of 3 mm / 3 % . The reduction magnitudes of maximum and mean dose to various OARs ranged between 0.06 % ∼ 6.76 % ( 0.04 ∼ 7.29 Gy ) and 0.09 % ∼ 7.81 % ( 0.02 ∼ 2.78 Gy ), respectively, using jaw tracking, agreeing with the disparities of radiological characteristics between MLC and jaws. Jaw tracking does not change the delivery efficiency and total monitor units. The dosimetric comparison of VMAT plans with and without jaw tracking confirms the physics hypotheses that reduced transmission through tracking jaws will reduce doses to OARs without sacrificing the target dose coverage because it is meant to be covered by radiation beams going through the opening. PACS number(s): 87.55.de, 87.55.dk